The use of the partograph in labor monitoring: a cross-sectional study among obstetric caregivers in General Hospital, Calabar, Cross River State, Nigeria - Asibong U; Okokon IB; Agan TU; Oku A; Opiah M; Essien EJ; Monjok E (Dove Medical Press, 2014)
Udeme Asibong,1 Ita B Okokon,1 Thomas U Agan,2 Affiong Oku,3 Margaret Opiah,4 E James Essien,5 Emmanuel Monjok1,5 1Department of Family Medicine, College of Medical Sciences, University of Calabar and University of Calabar Teaching Hospital, Calabar, Nigeria; 2Department of Obstetrics and Gynecology, College of Medical Sciences, University of Calabar and University of Calabar Teaching Hospital, Calabar, Nigeria; 3Department of Community Medicine, College of Medical Sciences, University of Calabar and University of Calabar Teaching Hospital, Calabar, Nigeria; 4Department of Maternal and Child Health, Faculty of Nursing, Niger Delta University, Wilberforce Island, Bayelsa State, Nigeria; 5Institute of Community Health, University of Houston, Texas Medical Center, Houston, TX, USA Background: Prolonged and obstructed labor is a significant cause of maternal morbidity and mortality in Nigeria, one of the six countries contributing significantly to the global maternal mortality crisis. The use of the partograph would engender a remarkable reduction in the number of these deaths since abnormal markers in the progress of labor would be identified early on. Objective: This study aimed to evaluate the non-physician obstetric caregivers’ (OCGs) knowledge of partograph use, assess the extent of its use, determine the factors that impede its usage, and unravel the relationship between years of experience and partograph use among the respondents (OCGs) in General Hospital, Calabar, Nigeria. Methodology: Using a self-administered semi-structured questionnaire, a cross-sectional descriptive study was conducted among 130 purposely selected and consenting OCGs working in the General Hospital, Calabar, Nigeria. Results: The majority of the respondents (70.8%) had good general knowledge of the partograph but lacked detailed and in-depth knowledge of the component parts of the partograph. Knowledge of partograph (χ2=12.05, P=0.0001) and partograph availability (χ2=56.5, P=0.0001) had a significant relationship with its utilization. Previous training (χ2=9.43, P=0.002) was significantly related to knowledge of partograph. Factors affecting utilization were: little or no knowledge of the partograph (85.4%), nonavailability (70%), shortage of staff (61.5%), and the fact that it is time-consuming to use (30%). Conclusion: Lack of detailed knowledge of the partograph, nonavailability of the partograph, poor staff numbers, and inadequate training are factors that work against the effective utilization of the partograph in the study facility. Usage of this tool for labor monitoring can be enhanced by periodic training, making partographs available in labor wards, provision of reasonable staff numbers, and mandatory institutional policy. Keywords: knowledge, utilization, partograph, obstetric caregivers, labor monitoring, Nigeria